Agent oriented requirement engineering for lake mathematical modelling: Preliminary study - Cheah, Wai Shiang; Sim, Yee Wai; Shane, Nizam; Loh, Chee Wyai (Universiti Teknikal Malaysia Melaka, 2016)
Agent oriented requirement engineering (AORE) is useful in transforming mathematical models to agent oriented modelling and simulation. The transformation process is based on a requirement elicitation study in which various stakeholders will understand users' requirements through elicitation questions and interviews. The AORE enable the modellers to understand the mathematical model and translate the model into the agent context. With AORE, the computational science students can enjoy the benefits of agent modelling and simulation during their study. This paper presents the work to guide the computational science and mathematical students in agent based simulation. It presents a method to transform the discrete mathematical model into individual based modelling and simulation. Consequently, the method is able to promote the agent technology to a wider audience. We proposed an extended version of AORE that can offer requirements elicitation support in environmental modelling, a computational science (CS) domain of study. The mechanism of AORE within a state of the art agent oriented methodology (AOM) is presented in details through a lake modelling case study in this paper. Also, a demonstration on simulating the case study in agent simulation, NetLogo, and comparison with the origin simulation results of lake model is elaborated to validate the feasibility of AORE.